A Difference Between Bedtime and Pre-Breakfast Plasma Glucose Levels Indicates the Need for Prandial Insulin in Basal Insulin-Treated Type 2 Diabetic Patients with Normal Fasting Glucose - Kress S (Dove Medical Press, 2021)
Stephan Kress,1 Anja Borck,2 Ariel Zisman,3 Peter Bramlage,4,5 Thorsten Siegmund6 1Diabeteszentrum, Vinzentius-Krankenhaus, Landau, Germany; 2Medical Department, Sanofi, Berlin, Germany; 3The Endocrine Center of Aventura, Aventura, FL, USA; 4Institute for Pharmacology and Preventive Medicine, Cloppenburg, Germany; 5Department for Angiology, Brandenburg Medical School, Campus Brandenburg/Havel, Brandenburg, Germany; 6Diabetes- Hormon- Und Stoffwechselzentrum Am Isar Klinikum München, München, GermanyCorrespondence: Stephan KressDiabeteszentrum, Vinzentius Krankenhaus, Cornichonstr. 4, Landau, 76829, GermanyTel +49 6341 172208Email kress.innere@vinzentius.deAim: In the present analysis, we characterised the efficacy and safety of adding a single daily injection of insulin glulisine to optimised basal-supported oral therapy (BOT) in patients with a high BeAM value, defined as a more than 50 mg/dl difference between bedtime and pre-breakfast blood glucose.Methods: The BeAM value was retrospectively calculated for patients pooled from two clinical trials that supplemented BOT with glulisine. Data regarding changes in HbA1c, fasting plasma glucose (FPG), and postprandial glucose (PPG) levels from observation periods of 3 to 6 months were assessed.Results: Out of 358 patients that received BOT/glulisine, 182 had a high BeAM value. Patients with a high BeAM value were older and had a longer diabetes duration than patients with a medium BeAM value. Significant reductions in HbA1c (7.5% to 7.2% [59 to 55 mmol/mol], p< 0.0001) and PPG (202 to 143 mg/dl, p< 0.0001) levels were documented. The proportion of patients with a high BeAM value achieving an HbA1c < 7% [53 mmol/mol], alone or in combination with no hypoglycaemia, was lower than that of patients with a medium BeAM value.Conclusion: The analysis indicates that the supplementation of BOT with a single daily injection of prandial insulin is safe and effective for reducing HbA1c and PPG levels in patients with a high BeAM value (more than 50 mg/dl). However, patients with a medium BeAM value also responded well, which suggests that they should also be considered candidates for this change in therapy.Keywords: basal-plus, prandial insulin, type-2 diabetes, glulisine, glargine